Corneal Abrasions in Total Joint Arthroplasty - Megan E. Young BS (SAGE Publishing, 2021)
Introduction Corneal abrasion (CA) is the most common ocular complication in patients undergoing nonocular surgery. Corneal abrasions can be caused by a variety of mechanisms, the most common being drying of the cornea due to reduced tear secretions, loss of eyelid reflex, and the loss of pain recognition during surgery. Though CA heals well with eye lubricants, it can result in significant ocular pain and some cases may go on to develop ocular complications. With the current switch to outpatient total joint replacement, CA could potentially lead to discharge delays. Materials and Methods We examined the results of a quality improvement project to reduce CA during general anesthesia to determine the rates of CA during hip and knee total joint replacement. We compared rates of CA for 6 months before and 6 months after the intervention. Results A total of 670 hip and knee arthroplasty procedures were performed during this period. Two events of CA occurred, one occurred before and one after the intervention to decrease eye injuries. Both incidences occurred during total hip arthroplasty (THA) procedures with the patient in the lateral decubitus position and recovered without long-term deficit. Discussion Surgeons and anesthesiologists alike should be cognizant of this avoidable complication and take precaution to protect the eyes during surgery, especially during THA when the patient is placed in the lateral decubitus position. Conclusion Corneal abrasion during total joint arthroplasty is a rare complication and is infrequently addressed in the literature. CA is mostly self-limiting, however, but may lead to patient dissatisfaction and to delays if same-day discharge is attempted. Preventative measures and attentive care may help reduce the incidence of CA in patients undergoing total joint arthroplasty. The lateral decubitus position and longer surgeries times are risk factors for CA.